2016
DOI: 10.1007/s12520-016-0413-1
|View full text |Cite
|
Sign up to set email alerts
|

Shell we cook it? An experimental approach to the microarchaeological record of shellfish roasting

Abstract: In this paper, we investigate the microarchaeological traces and archaeological visibility of shellfish cooking activities through a series of experimental procedures with direct roasting using wood-fueled fires and controlled heating in a muffle furnace. An interdisciplinary geoarchaeological approach, combining micromorphology, FTIR (in transmission and ATR collection modes), TGA and XRD, was used to establish a baseline on the mineralogical transformation of heated shells from aragonite to calcite and diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 51 publications
5
38
0
Order By: Relevance
“…These are artifacts or sediments altered because of fire temperatures. Depending on the temperature threshold, such heating can result in important structural and mineralogical transformations (Aldeias et al 2016a(Aldeias et al , 2016bChu et al 2008;Elbaum et al 2003;Maki, Homburg, and Brosowske 2006;Schmidt 2013;Schmidt et al 2013;Stiner et al 1995;Toffolo and Boaretto 2014;Weiner et al 2015). Therefore, thermally altered artifacts (bones, lithics, shells, seeds, etc.…”
Section: Fire Proxies and Their Contextual Arrangementmentioning
confidence: 99%
See 1 more Smart Citation
“…These are artifacts or sediments altered because of fire temperatures. Depending on the temperature threshold, such heating can result in important structural and mineralogical transformations (Aldeias et al 2016a(Aldeias et al , 2016bChu et al 2008;Elbaum et al 2003;Maki, Homburg, and Brosowske 2006;Schmidt 2013;Schmidt et al 2013;Stiner et al 1995;Toffolo and Boaretto 2014;Weiner et al 2015). Therefore, thermally altered artifacts (bones, lithics, shells, seeds, etc.…”
Section: Fire Proxies and Their Contextual Arrangementmentioning
confidence: 99%
“…Of particular interest is the identification of syndepositional (i.e., after formation and before burial) human interactions with fire residues, as such data can give us information on space use, maintenance activities, and, at times, fire functions. For instance, in our experimental work with hearths used for roasting shellfish, Aldeias et al (2016b) showed that spreading and dumping of fire residues outside the cooking area was an essential step in the cooking procedures. Such actions resulted in the absence of a microstratigraphy associated with intact hearths, which in this case would not be due to poor preservation of the fire features but because removal of combustion residues was an intentional activity that directly related to hearth use.…”
Section: The Role Of Anthropic Actionsmentioning
confidence: 99%
“…Also artefacts, such as a broken vessel, fragments of different vessels, polishing stones, and some bone tools, were also found. On the basis of experimental studies (e.g., Aldeias, Gur‐Arieh, Maria, Monteiro, & Cura, ), archaeologists assume that the pit might have been used for heating Unio sp. shells (Dolbunova et al, in print).…”
Section: Methodsmentioning
confidence: 99%
“…A similar approach was used by Villagran (2014) with Anomalocardia brasiliana (venus clam) shells. Aldeias, Gur‐Arieh, Maria, Monteiro, and Cura (2019) characterized the recrystallization of aragonite into calcite upon heating in different species to investigate shellfish roasting from an experimental standpoint and with the aid of FTIR, µFTIR, XRD, and micromorphology. Karkanas et al (2019) characterized with µFTIR the mineralogy of fossil aragonitic oolites embedded in the construction material of a Late Bronze Age pottery kiln in Greece to distinguish unaltered areas (aragonite) from areas affected by elevated temperatures (calcite).…”
Section: Archaeological Significancementioning
confidence: 99%